Effects of Prone Positioning on Respiratory Mechanics and Oxygenation in Critically Ill Patients With COVID-19 Requiring Venovenous Extracorporeal Membrane Oxygenation - Laghlam, Driss; Charpentier, Julien; Hamou, Zakaria Ait; Nguyen, Lee S.; Pene, Frédéric; Cariou, Alain; Mira, Jean-Paul; Jozwiak, Mathieu (Frontiers in Medicine, 2022)
Background: The effect of prone positioning (PP) on respiratory mechanics remains uncertain in patients with severe acute respiratory distress syndrome (ARDS) requiring venovenous extracorporeal membrane oxygenation (VV-ECMO). Methods: We prospectively analyzed the PP effects on respiratory mechanics from continuous data with over a thousand time points during 16-hour PP sessions in COVID-19 patients with ARDS under VV-ECMO. The evolution of the respiratory mechanical and oxygenation parameters during PP sessions was evaluated by dividing each PP session into four-time quartiles: first quartile: 0-4 hours, second quartile: 4-8 hours, third quartile: 8-12 hours and fourth quartile: 12-16 hours. Results: Overall, 38 PP sessions were performed in 10 patients with 3[2-5] PP sessions per patient. Seven (70%) patients were responders to at least one PP session. PP significantly increased the PaO2/FiO2 ratio by 14±21% and the compliance by 8±15% and significantly decreased the oxygenation index by 13±18% and the driving pressure by 8±12%. PP effects on respiratory mechanics but not on oxygenation persisted after supine repositioning. PP-induced changes in the different respiratory mechanical parameters and oxygenation started as early as the first-time quartile, without any difference in PP-induced changes between the different time quartiles. PP-induced changes in driving pressure (-14±14 vs. -6±10%, p=0.04) and in mechanical power (-11±13 vs. -0.1±12%, p=0.02) were significantly higher in responders (increase in PaO2/FiO2 ratio>20%) than in non-responder patients. Conclusions: In COVID-19 patients with severe ARDS, PP under VV-ECMO improved the respiratory mechanical and oxygenation parameters and PP effects on respiratory mechanics persisted after supine repositioning.